OPTIMIZING THE ROLE OF FAMILY EMPOWERMENT AND WELFARE CADRES THROUGH FOOD PRODUCT INNOVATION AND NUTRITIONAL LITERACY IN PENGGILINGAN URBAN SUBURBS, CAKUNG, EAST JAKARTA - Nugraha, Ananditya; Anngrainy, Hanny; Wibisono, Kenneth Francis; Siaurat Kaawoan, Leonard Davinci; Haidi, Bianca; Wiria, Sheila Zivana; Theodosius, Timothy; Hasanah, Fathiyah Mumtaz (Universitas Padjadjaran, 2026)
In Indonesia, Kelompok Pemberdayaan dan Kesejahteraan Keluarga (PKK), or Family Empowerment and Welfare cadres, play a crucial role as grassroots agents in disseminating health- and livelihood-related knowledge to the wider community. This community service program aimed to optimize the role of PKK cadres in Penggilingan Urban Village, Cakung, East Jakarta, through integrated training on food product development. The community service program was conducted from July to December 2025, involving twenty PKK cadres through seminars, hands-on workshops, and a benchmarking field visit to Rumah Tempe Indonesia. Program effectiveness was evaluated using pre- and post-tests at each major activity. The results showed consistent improvements in post-test scores across all sessions. The post-test scores were higher than the pre-test scores across all topics, indicating an overall improvement. For instance, Food Hygiene and Safety increased from 4.42 to 4.84, Profit-Smart Kitchen from 4.39 to 4.62, Hypertension from 3.71 to 3.93, Food Safety and Packaging from 3.39 to 4.36, and Food Additives from 4.38 to 4.50. However, statistically significant increases (p < 0.05) were only observed in the Food Hygiene and Safety (p = 0.011) and Food Safety and Packaging (p = 0.007) topics, while the other topics showed non-significant gains. Overall, these findings indicate that experiential learning approaches combining theoretical instruction and practical application are effective in improving PKK cadres’ capacity in food product development-related skills.Di Indonesia, kader Pemberdayaan dan Kesejahteraan Keluarga (PKK) memiliki peran penting sebagai agen dalam diseminasi pengetahuan terkait kesehatan dan penghidupan kepada masyarakat lebih luas Pemberdayaan kader PKK melalui pembekalan ilmu pangan dan pengetahuan gizi akan memberikan manfaat bagi masyarakat. Program pengabdian kepada masyarakat ini bertujuan untuk mengoptimalkan peran kader PKK di Kelurahan Penggilingan, Jakarta Timur, melalui pelatihan terintegrasi yang mencakup pengembangan produk pangan. Program dilaksanakan pada periode Juli hingga Desember 2025 dengan melibatkan 20 kader PKK melalui kegiatan seminar, lokakarya praktik, serta kunjungan pembelajaran ke Rumah Tempe Indonesia. Evaluasi efektivitas program dilakukan menggunakan pre-test dan post-test pada setiap kegiatan utama. Hasil evaluasi menunjukkan adanya peningkatan skor post-test secara konsisten pada seluruh sesi, dengan peningkatan yang signifikan terutama pada materi kebersihan, keamanan pangan, dan pengemasan. Skor post-test lebih tinggi dibandingkan dengan pre-test pada seluruh topik, yang menunjukkan adanya peningkatan secara keseluruhan; sebagai contoh, Food Hygiene and Safety meningkat dari 4,42 menjadi 4,84, Profit-Smart Kitchen dari 4,39 menjadi 4,62, Hypertension dari 3,71 menjadi 3,93, Food Safety and Packaging dari 3,39 menjadi 4,36, serta Food Additives dari 4,38 menjadi 4,50. Peningkatan yang signifikan secara statistik (p < 0,05) hanya terdapat pada topik terkait Food Hygiene and Safety (p = 0,011) dan Food Safety and Packaging (p = 0,007). Secara keseluruhan, program ini menunjukkan bahwa pendekatan pembelajaran berbasis pengalaman yang mengintegrasikan teori dan praktik efektif dalam meningkatkan kapasitas kader PKK untuk mengembangkan produk pangan.